High-stripping low-dielectric hydrocarbon resin glue solution, preparation method thereof, prepreg and copper-clad plate
By adding pre-crosslinking systems and 1-iodonaphthalene modified polybutene to the hydrocarbon resin glue, the problems of insufficient rigidity, low peeling and poor heat resistance in the field of copper clad plates are solved, and copper clad plate products with high peel strength, excellent heat resistance and low dielectric properties are achieved, which improves its comprehensive performance and service life.
Patent Information
- Application Number
- CN202411562598.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-25
AI Technical Summary
The application of existing hydrocarbon resins in the field of copper clad plates is limited by their insufficient rigidity, low peeling, poor heat resistance, etc., which leads to prone to embrittlement and aging in high temperature and high humidity environments, affecting the stability and service life of copper clad plates.
A high-peel and low-dielectric hydrocarbon resin glue solution is used, including pre-crosslinking system, 1-iodonaphthalene modified polybutene, hydrocarbon resin, inorganic filler, initiator, accelerator and solvent. Through the combination of these components, the formed glue solution has good dispersion and processing properties and is used to prepare copper clad plates.
It has achieved high peel strength, excellent heat resistance and low dielectric performance, which has improved the comprehensive performance and service life of copper clad plate.
Smart Images

Figure BDA0005118287410000091 
Figure BDA0005118287410000101 
Figure HDA0005118287420000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to a high-stripping and low-dielectric hydrocarbon resin adhesive and a preparation method thereof, a prepreg and a copper clad laminate. Background Art
[0002] With the advent of the 5G communication era and the continuous development of electronic products, people have higher and higher requirements for the performance of copper clad laminates. Among them, thermal conductivity is one of the important indicators of copper clad laminates. In traditional copper clad laminate materials, resin-based materials have poor thermal conductivity, which will cause them to easily overheat under high-power working conditions, thereby affecting the stability and service life of the copper clad laminate. Therefore, research and development of a resin-based material with high thermal conductivity is of great significance to improving the performance of copper clad laminates.
[0003] Hydrocarbon resin has excellent dielectric properties, corrosion resistance and comprehensive performance, and is low in cost. It is an ideal material for preparing copper clad laminates. By adding various additives to the hydrocarbon resin system, its dielectric properties, mechanical properties, thermal conductivity and other properties can be changed. However, the application of hydrocarbon resin in the field of copper clad laminates is still relatively small. The main reason is that hydrocarbon resin has a flexible, non-polar carbon chain structure, which leads to problems such as insufficient rigidity, low peeling, and poor heat resistance in the cured product. Not only is it prone to embrittlement and aging in high temperature and high humidity environments, causing the copper clad laminate to fail, but also the dispersibility and processing performance in resin-based materials are poor, thus limiting its use. Summary of the invention
[0004] In order to solve the above technical problems existing in the prior art, the present invention provides a high-peeling and low-dielectric hydrocarbon resin adhesive and a preparation method thereof, a prepreg and a copper-clad laminate.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] The first aspect of the present invention is to provide a high-peeling and low-dielectric hydrocarbon resin adhesive, comprising the following components: a pre-crosslinking system, 1-iodonaphthalene-modified polybutene, a hydrocarbon resin, an inorganic filler, an initiator, a promoter and a solvent; the pre-crosslinking system is a product of a mixed liquid of polyphenylene ether and polybutene modified by a modifier.
[0007] On the basis of the above technical solution, the present invention can also make the following improvements:
[0008] Furthermore, the weight proportions of the components are: 30-40 parts of the pre-crosslinking system, 75-100 parts of 1-iodonaphthalene modified polybutene, 60-80 parts of hydrocarbon resin, 15-30 parts of inorganic filler, 50-70 parts of initiator, 0.03-0.05 parts of accelerator, and 80-100 parts of solvent.
[0009] By adopting the above technical scheme of the present invention, the pre-crosslinking system can enhance the anti-peeling property of the copper clad laminate product after curing and improve the peeling strength; the 1-iodonaphthalene-modified polybutene resin can enhance the heat resistance of the copper clad laminate product; the hydrocarbon resin has excellent electrical properties, and the pre-crosslinking system, the 1-iodonaphthalene-modified polybutene resin, and the hydrocarbon resin are matched with each other and other components are added to form a glue with good dispersibility and processing performance. The glue is used for the preparation of copper clad laminates to obtain copper clad laminate products with high peeling strength, excellent heat resistance and low dielectric properties.
[0010] Furthermore, the weight ratio of the pre-crosslinking system, 1-iodonaphthalene-modified polybutene, and hydrocarbon resin is 1:2-3:1.5-2.5, preferably 1:2.5:2.
[0011] The beneficial effect of adopting the above further technical scheme is that the weight ratio of the pre-crosslinking system, 1-iodonaphthalene modified polybutene and hydrocarbon resin is limited to 1:2-3:1.5-2.5, the obtained resin system is used to prepare copper clad laminates, and the final copper clad laminates have excellent comprehensive properties.
[0012] The hydrocarbon resin is any one of polypropylene resin, polystyrene resin, polybutadiene resin, and polyisobutadiene resin, or a mixture of two or more thereof; the inorganic filler is magnesium hydroxide; the initiator is di-tert-butyl peroxide; the accelerator is 2-ethyl-4-methylimidazole; and the solvent includes any one or more of acetone, butanone, and toluene.
[0013] Furthermore, the preparation of the pre-crosslinking system includes the following steps: using solvent A to dissolve the polyphenylene ether and polybutylene to obtain a mixed solution A, adding a modifier and an initiator A to the mixed solution A, heating to 70-80° C. under nitrogen purge conditions, reacting for 2.5-3 hours, and obtaining a pre-crosslinking system. The modifier is benzonitrile.
[0014] Furthermore, the mass ratio of the polyphenylene ether to the polybutylene is 1.5-2.5:1, preferably 2:1.
[0015] The added amount of the polyphenylene ether is 80-100g, the added amount of the polybutene is 40-50g, the added amount of the solvent A is 60-100g, and the added amount of the initiator A is 0.17-0.3g; the solvent A is toluene and / or butanone, and the initiator A is azobisisobutyronitrile.
[0016] Specifically, in a dry and clean 250mL beaker, add 80-100g of polyphenylene ether and 40-50g of polybutene, add 60-100g of solvent toluene, stir to completely dissolve, and obtain a mixed solution A. Take 100g of the mixed solution A and add 5.0-5.5g of the modifier, add 0.17-0.3g of azobisisobutyronitrile (AIBN), gradually heat to 70-80°C under nitrogen purge conditions, react for 2.5-3h, and obtain a pre-crosslinked system.
[0017] The polyphenylene ether used is polyphenylene ether resin SA9000 produced by SABIC, which is a low molecular weight polyphenylene ether resin powder.
[0018] Furthermore, the preparation of the 1-iodonaphthalene modified polybutene includes the following steps: using solvent B to dissolve polybutene, 1-iodonaphthalene, palladium acetate, and triethylamine to obtain a mixed solution B; heating the mixed solution B to 90-110° C. under a nitrogen atmosphere, reacting for 18-24 hours, and obtaining 1-iodonaphthalene modified polybutene.
[0019] Furthermore, the mass ratio of the modified polybutene: 1-iodonaphthalene: palladium acetate: triethylamine is 10-20: 20-40: 1: 15-30, preferably 20: 40: 1: 30.
[0020] The added amount of the polybutene is 50-100g, the added amount of 1-iodonaphthalene is 100-200g, the added amount of palladium acetate is 2.5-5g, the added amount of triethylamine is 75-150g, and the added amount of solvent B is 150-200g; the solvent B is N,N-dimethylformamide.
[0021] Specifically, the Heck reaction is used to react the polybutene resin with 1-iodonaphthalene: in a dry and clean 100mL single-necked flask, add 50-100g of polybutene, 100-200g of 1-iodonaphthalene, 2.5-5g of palladium acetate (Pd(OAc)2), 75-150g of triethylamine, and 150-200g of N,N-dimethylformamide (DMF), gradually heat to 90-100°C under a nitrogen atmosphere, react for 18-24h, and obtain 1-iodonaphthalene-modified polybutene.
[0022] The second aspect of the present invention is to provide a method for preparing the above-mentioned hydrocarbon resin glue, comprising the following steps: preparing a pre-crosslinking system and 1-iodonaphthalene modified polybutene respectively; mixing the prepared pre-crosslinking system, 1-iodonaphthalene modified polybutene and hydrocarbon resin to form a blended resin; adding inorganic filler, initiator, promoter, solvent to the blended resin and mixing them to prepare hydrocarbon resin glue.
[0023] The third aspect of the present invention is to provide a semi-cured sheet, the preparation process of which is: immersing the glass fiber cloth in the above-mentioned hydrocarbon resin adhesive or coating the above-mentioned hydrocarbon resin adhesive on the glass fiber cloth, and then baking and curing the glass fiber cloth to obtain the semi-cured sheet, and the thickness of the semi-cured sheet is 1-10mm.
[0024] The glass fiber cloth impregnated or coated with hydrocarbon resin glue is cured by baking at 120-150°C for 4-5 minutes to obtain a semi-cured sheet.
[0025] Another aspect of the present invention is to provide a copper clad laminate, the preparation process of which is: taking 2-8 prepregs and stacking them in sequence, covering both sides of the prepregs with copper foil, and preparing the copper clad laminate after lamination.
[0026] The lamination process conditions are: lamination temperature 180-260°C, lamination pressure 2-7MPa, and lamination time 2-8h.
[0027] Compared with the prior art, the present invention has the following technical effects:
[0028] The adhesive for preparing copper clad laminates of the present invention can enhance the peeling resistance and processability of the copper clad laminate products after curing by adding a pre-crosslinking system, the modified polybutene resin can enhance the heat resistance of the product and improve the rigidity, and the hydrocarbon resin has excellent electrical properties; the pre-crosslinking system, the 1-iodonaphthalene-modified polybutene resin, and the hydrocarbon resin are matched with each other and other components are added to form an adhesive with good dispersibility and processability, and the adhesive is used for preparing copper clad laminates to obtain copper clad laminate products with high peeling strength, excellent heat resistance, and low dielectric properties;
[0029] The pre-crosslinking system contains hydrocarbons, the modified polybutylene resin also contains hydrocarbons, and the base resin is a hydrocarbon resin. The mixture of the three hydrocarbon-containing resins can enhance the dispersion performance of the resin system and make the resin system more evenly dispersed. The three work together to improve the overall performance of the final copper clad laminate product. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The nuclear magnetic resonance spectrum of 1-iodonaphthalene modified polybutene is shown;
[0031] Figure 2 The electron microscope photos of the copper clad laminates prepared in the examples are: (a) Example 1, (b) Example 3, (c) Example 2;
[0032] Figure 3 The following are electron microscope photos of the copper clad laminates prepared in the comparative examples: (d) comparative example 2, (e) comparative example 3, and (f) comparative example 1. DETAILED DESCRIPTION
[0033] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0034] Example 1
[0035] (1) Preparation of a pre-crosslinking system: In a dry and clean 250 mL beaker, add 80 g of polyphenylene ether and 40 g of polybutene, add 60 g of solvent toluene, stir to completely dissolve, and obtain a mixed solution A. Take 100 g of the mixed solution A, add 5.0 g of benzonitrile, add 0.17 g of azobisisobutyronitrile (AI BN), gradually heat to 70° C. under nitrogen purge, and react for 2.5 h to obtain a pre-crosslinking system.
[0036] (2) Preparation of 1-iodonaphthalene-modified polybutene: The Heck reaction was used to react the polybutene resin with 1-iodonaphthalene. In a dry and clean 100-mL single-necked flask, 50 g of polybutene, 100 g of 1-iodonaphthalene, 2.5 g of palladium acetate, 75 g of triethylamine, and 150 g of N,N-dimethylformamide were added. The mixture was gradually heated to 100° C. under a nitrogen atmosphere and reacted for 18 h to obtain 1-iodonaphthalene-modified polybutene.
[0037] (3) Preparation of hydrocarbon resin adhesive: 30 parts of pre-crosslinking system, 75 parts of 1-iodonaphthalene modified polybutene, 60 parts of hydrocarbon resin (a blended resin composed of polypropylene resin and polystyrene resin, including 30 parts of polypropylene resin and 30 parts of polystyrene resin), 15 parts of magnesium hydroxide, 50 parts of di-tert-butyl peroxide, 0.03 parts of 2-ethyl-4-methylimidazole, 80 parts of acetone, butanone and toluene are dissolved and mixed in a mixed solvent to obtain hydrocarbon resin adhesive.
[0038] (4) Preparing a prepreg: coating a hydrocarbon resin adhesive on a glass fiber cloth and baking at 130° C. for 5 min to obtain a prepreg;
[0039] (5) Preparation of copper clad laminate: Take 6 semi-cured sheets with flat surfaces and uniform coating prepared in the above (4), stack them neatly, attach copper foil on the top and bottom, and place them in a vacuum hot press preheated to 140°C, with a lamination temperature of 220°C, a lamination pressure of 4 MPa, and a lamination time of 3 h to obtain a copper clad laminate.
[0040] Example 2
[0041] (1) Preparation of a pre-crosslinking system: In a dry and clean 250 mL beaker, add 100 g of polyphenylene ether and 50 g of polybutene, and add a total of 100 g of solvent toluene and butanone, and stir to completely dissolve them to obtain a mixed glue solution A. Take 100 g of the mixed solution A, add 5.5 g of benzonitrile, add 0.2 g of azobisisobutyronitrile (AI BN), gradually heat to 80° C. under nitrogen purge conditions, and react for 3 h to obtain a pre-crosslinking system.
[0042] (2) Preparation of 1-iodonaphthalene-modified polybutene: The Heck reaction was used to react polybutene resin with 1-iodonaphthalene. In a dry and clean 100-mL single-necked flask, 100 g of polybutene, 200 g of 1-iodonaphthalene, 5 g of palladium acetate, 150 g of triethylamine, and 200 g of N,N-dimethylformamide were added. The mixture was gradually heated to 100° C. in a nitrogen atmosphere and reacted for 24 h to obtain 1-iodonaphthalene-modified polybutene.
[0043] (3) Preparation of hydrocarbon resin adhesive: 40 parts of a pre-crosslinking system, 100 parts of 1-iodonaphthalene-modified polybutene, 65 parts of a hydrocarbon resin (a blended resin composed of polybutadiene resin and polyisobutadiene resin, including 30 parts of polybutadiene resin and 35 parts of polyisobutadiene resin), 30 parts of magnesium hydroxide, 70 parts of di-tert-butyl peroxide, 0.05 parts of 2-ethyl-4-methylimidazole, and 100 parts of a solvent (a mixed solvent composed of toluene and butanone) are dissolved and mixed to prepare a hydrocarbon resin adhesive.
[0044] (4) Preparation of semi-cured sheet: Apply hydrocarbon resin glue on glass fiber cloth and bake at 130°C for 5 minutes to obtain a semi-cured sheet.
[0045] (5) Preparation of copper clad laminate: Take 6 prepregs with smooth surface and uniform coating prepared in (4) above, stack them neatly, attach copper foil on the top and bottom, and place them in a vacuum hot press preheated to 140°C, with a lamination temperature of 220°C, a lamination pressure of 4 MPa, and a lamination time of 3 h to obtain a copper clad laminate.
[0046] Example 3
[0047] (1) Preparation of a pre-crosslinking system: In a dry and clean 250 mL beaker, add 80 g of polyphenylene ether and 40 g of polybutene, add 60 g of solvent toluene, stir to completely dissolve, and obtain a mixed solution A. Take 100 g of the mixed solution A, add 5.0 g of benzonitrile, add 0.17 g of azobisisobutyronitrile (AI BN), gradually heat to 70° C. under nitrogen purge, and react for 2.5 h to obtain a pre-crosslinking system.
[0048] (2) Preparation of 1-iodonaphthalene-modified polybutene: The Heck reaction was used to react the polybutene resin with 1-iodonaphthalene. In a dry and clean 100-mL single-necked flask, 50 g of polybutene, 100 g of 1-iodonaphthalene, 2.5 g of palladium acetate, 75 g of triethylamine, and 150 g of N,N-dimethylformamide were added. The mixture was gradually heated to 100° C. under a nitrogen atmosphere and reacted for 18 h to obtain 1-iodonaphthalene-modified polybutene.
[0049] (3) Preparation of hydrocarbon resin adhesive: 30 parts of pre-crosslinking system, 65 parts of 1-iodonaphthalene modified polybutene, 70 parts of hydrocarbon resin (a blended resin composed of polypropylene resin and polystyrene resin, including 30 parts of polypropylene resin and 40 parts of polystyrene resin), 15 parts of magnesium hydroxide, 50 parts of di-tert-butyl peroxide, 0.03 parts of 2-ethyl-4-methylimidazole, 80 parts of acetone, a mixed solvent composed of butanone and toluene were dissolved and mixed to obtain hydrocarbon resin adhesive.
[0050] (4) Preparing a prepreg: coating a hydrocarbon resin adhesive on a glass fiber cloth and baking at 130° C. for 5 min to obtain a prepreg;
[0051] (5) Preparation of copper clad laminate: Take 6 semi-cured sheets with flat surfaces and uniform coating prepared in the above (4), stack them neatly, attach copper foil on the top and bottom, and place them in a vacuum hot press preheated to 140°C, with a lamination temperature of 220°C, a lamination pressure of 4 MPa, and a lamination time of 3 h to obtain a copper clad laminate.
[0052] Comparative Example 1
[0053] (1) Preparation of 1-iodonaphthalene modified polybutene: The Heck reaction was used to react polybutene resin with 1-iodonaphthalene. In a dry and clean 100 ml single-necked flask, 50 g of polybutene, 100 g of 1-iodonaphthalene, 2.5 g of palladium acetate, 75 g of triethylamine, and 150 g of N,N-dimethylformamide were added. The mixture was gradually heated to 100° C. in a nitrogen atmosphere and reacted for 18 h to obtain modified polybutene.
[0054] (2) Preparation of hydrocarbon resin glue: 30 parts of polybutene, 60 parts of 1-iodonaphthalene-modified polybutene, 60 parts of a blend of polypropylene resin and polystyrene resin, 15 parts of magnesium hydroxide, 50 parts of di-tert-butyl peroxide, 0.03 parts of 2-ethyl-4-methylimidazole, and 80 parts of acetone were dissolved and mixed to obtain a hydrocarbon resin glue.
[0055] (3) Preparation of semi-cured sheet: Apply hydrocarbon resin glue on glass fiber cloth and bake at 130°C for 5 minutes to obtain a semi-cured sheet.
[0056] (4) Preparation of copper clad laminate: Take 6 semi-cured sheets with flat surfaces and uniform coating prepared in the above (3), stack them neatly, attach copper foil on the top and bottom, and place them in a vacuum hot press preheated to 140°C, with a lamination temperature of 220°C, a lamination pressure of 4 MPa, and a lamination time of 3 h to obtain a copper clad laminate.
[0057] Comparative Example 2
[0058] (1) Preparation of a pre-crosslinking system: In a dry and clean 250 ml beaker, add 80 g of polyphenylene ether, 40 g of polybutene and 60 g of solvent toluene, stir to completely dissolve them to obtain a mixed solution, take 100 g of the mixed solution and add 5.0 g of benzonitrile and 0.17 g of azobisisobutyronitrile (AIBN) thereto, gradually heat to 70° C. under nitrogen purge conditions, react for 2.5 hours, and obtain a pre-crosslinking system.
[0059] (2) Preparation of hydrocarbon resin glue: 30 parts of pre-crosslinking system, 60 parts of polybutene, 60 parts of polypropylene resin and polystyrene resin blended resin, 15 parts of magnesium hydroxide, 50 parts of di-tert-butyl peroxide, 0.03 parts of 2-ethyl-4-methylimidazole, and 80 parts of toluene solvent were dissolved and mixed to obtain hydrocarbon resin glue.
[0060] (3) Preparation of semi-cured sheet: Apply hydrocarbon resin glue on glass fiber cloth and bake at 130°C for 5 minutes to obtain a semi-cured sheet.
[0061] (4) Preparation of copper clad laminate: Take 6 prepregs with flat surfaces and uniform coating prepared in (3) above, stack them neatly, attach copper foils on the top and bottom, and place them in a vacuum hot press preheated to 140°C, with a lamination temperature of 220°C, a lamination pressure of 4 MPa, and a lamination time of 3 hours to obtain a copper clad laminate.
[0062] Comparative Example 3
[0063] (1) Preparation of hydrocarbon resin glue: 90 parts of polybutene, 60 parts of polypropylene resin and polystyrene resin blended resin, 15 parts of inorganic filler, 50 parts of initiator, 0.03 parts of accelerator, and 80 parts of toluene; dissolve and mix to prepare hydrocarbon resin glue.
[0064] (2) Preparation of semi-cured sheet: The resin was coated on glass fiber cloth and baked at 130°C for 5 minutes to obtain a semi-cured sheet.
[0065] (3) Preparation of copper clad laminate: Take 6 prepregs with flat surfaces and uniform coating prepared in (2) above, stack them neatly, attach copper foils on the top and bottom, and place them in a vacuum hot press preheated to 140°C, with a lamination temperature of 220°C, a lamination pressure of 4 MPa, and a lamination time of 3 h to obtain a copper clad laminate.
[0066] The 1H NMR spectrum of the 1-iodonaphthalene-modified polybutene resin prepared in step (2) of Example 1 was analyzed using a Varian DLG400 NMR spectrometer produced by Varian Company of the United States. A small amount of the 1-iodonaphthalene-modified polybutene product was transferred into a NMR tube, deuterated chloroform (CDCl3) was used as a solvent, and tetramethylsilane (TMS) was used as an internal standard. The NMR spectrum is shown in FIG. Figure 1 As shown in the figure, it can be seen that the peaks of 7.26-8.5ppm correspond to the hydrogen on the naphthyl group of the 1-iodonaphthalene molecule, and the peaks around 4.92ppm and 5.37ppm correspond to the hydrogen on the double bond of the polybutene side chain. The nuclear magnetic resonance spectrum shows that 1-iodonaphthalene was successfully connected to the polybutene resin and the modification was successful.
[0067] The performance comparison data of the copper clad laminates prepared in each embodiment and comparative example are shown in Table 1, wherein the test of glass transition temperature (DCS) is measured by a differential scanner of TA Instruments Waters, USA; the test of T288 thermal delamination time, thermal expansion coefficient, TE (50-260°C, Z axis) is measured by a thermomechanical analyzer of TA Instruments Waters, USA; the dielectric constant Dk (10GHz), dielectric constant Df (10GHz), dielectric constant Dk (5GHz), dielectric constant Df (5GHz) are measured by a network analyzer of KEYSIGHT, USA, and the peel strength is measured by a peel strength tester. The above test results are all based on the IPC TM-650 standard in the field of copper clad laminates.
[0068] Table 1 Experimental test results statistics
[0069]
[0070]
[0071] According to the data in the above table, we can clearly draw the following conclusions:
[0072] Compared with Examples 1-3, the comprehensive performance of the copper clad laminate samples obtained in Comparative Examples 1-3 is significantly reduced. Specifically, the dielectric constant and dielectric loss of Comparative Examples 1-3 are increased, especially the dielectric constant data of Comparative Example 3 are significantly increased, indicating that the addition of modified 1,2-polybutene pre-cross-linked resin and the combination with 1-iodonaphthalene modified polybutene in the present invention can improve the insulation performance of the copper clad laminate and reduce signal transmission loss;
[0073] Compared with Comparative Examples 1-3, the flame retardant properties of the copper clad laminate products obtained in Examples 1-3 are improved, indicating that the pre-crosslinking system and 1-iodonaphthalene-modified polybutene of the present invention can be added alone or in combination to improve the flame retardant properties, thereby extending the service life of the copper clad laminate;
[0074] Compared with Comparative Examples 1-3, the anti-peeling properties of the products obtained in Examples 1-3 are improved, indicating that the pre-crosslinking system for improving the anti-peeling effect of the present invention plays a certain role, and it is feasible to change the anti-peeling properties of the copper clad laminate by the pre-crosslinking system;
[0075] Compared with comparative examples 1-3, the heat resistance of the products obtained in examples 1-3 is enhanced, indicating that the addition of the pre-crosslinking system and modified polybutene of the present invention can enhance the heat resistance and high temperature resistance of the copper clad laminate.
[0076] according to Figure 2-3 ,from Figure 2 It can be seen from the figure that for the resin delamination phenomenon, (a) is better than (c) and better than (b). Both (b) and (c) have interfaces along the direction of the glass fiber, and (b) is obviously more serious. Figure 3 It can be seen that (d), (e) and (f) all have resin delamination, especially (e) and (f), and (e) has a higher probability of resin delamination. Therefore, according to the comparison, it can be obtained that the phase separation problem of the copper clad laminate prepared by the resin system with pre-crosslinking treatment has been significantly improved, indicating that pre-crosslinking treatment of the resin can significantly improve the phase separation problem of the copper clad laminate, thereby improving the processability of the copper clad laminate.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-peeling and low-dielectric hydrocarbon resin glue, characterized in that: The invention comprises the following components: a pre-crosslinking system, 1-iodonaphthalene modified polybutene, hydrocarbon resin, inorganic filler, initiator, accelerator and solvent; the pre-crosslinking system is a product of a mixed liquid of polyphenylene ether and polybutene modified by a modifier.
2. The high-peeling and low-dielectric hydrocarbon resin adhesive according to claim 1, characterized in that: The weight proportions of the components are: 30-40 parts of pre-crosslinking system, 75-100 parts of 1-iodonaphthalene modified polybutene, 60-80 parts of hydrocarbon resin, 15-30 parts of inorganic filler, 50-70 parts of initiator, 0.03-0.05 parts of accelerator and 80-100 parts of solvent.
3. The high-peeling and low-dielectric hydrocarbon resin adhesive according to claim 1 or 2, characterized in that: The weight ratio of the pre-crosslinking system, 1-iodonaphthalene modified polybutene and hydrocarbon resin is 1:2-3:1.5-2.
5.
4. The high-peeling and low-dielectric hydrocarbon resin adhesive according to claim 1 or 2, characterized in that: The preparation of the pre-crosslinking system comprises the following steps: using solvent A to dissolve the polyphenylene ether and polybutylene to obtain a mixed solution A, adding a modifier and an initiator A to the mixed solution A, heating to 70-80° C. under nitrogen purge conditions, reacting for 2.5-3 hours, and obtaining a pre-crosslinking system.
5. The high-peeling and low-dielectric hydrocarbon resin adhesive according to claim 4, characterized in that: The mass ratio of the polyphenylene ether and polybutylene added is 1.5-2:
1.
6. The high-peeling and low-dielectric hydrocarbon resin adhesive according to claim 1 or 2, characterized in that: The preparation of the 1-iodonaphthalene modified polybutene comprises the following steps: using solvent B to dissolve polybutene, 1-iodonaphthalene, palladium acetate and triethylamine to obtain a mixed solution B; heating the mixed solution B to 90-110° C. under a nitrogen atmosphere, reacting for 18-24 hours, and obtaining 1-iodonaphthalene modified polybutene.
7. The high-peeling and low-dielectric hydrocarbon resin adhesive according to claim 6, characterized in that: The mass ratio of the polybutene: 1-iodonaphthalene: palladium acetate: triethylamine added is 10-20: 20-40: 1: 15-30.
8. A method for preparing a high-stripping, low-dielectric hydrocarbon resin adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: A pre-crosslinking system and 1-iodonaphthalene modified polybutene are prepared respectively; the prepared pre-crosslinking system, 1-iodonaphthalene modified polybutene and hydrocarbon resin are mixed to form a blended resin; an inorganic filler, an initiator, a accelerator and a solvent are added to the blended resin and mixed to prepare a hydrocarbon resin glue.
9. A prepreg, characterized in that: The preparation process is: immersing the glass fiber cloth in the hydrocarbon resin adhesive described in any one of claims 1-7 or coating the hydrocarbon resin adhesive described in any one of claims 1-7 on the glass fiber cloth, and then baking and curing the glass fiber cloth to obtain the semi-cured sheet, and the thickness of the semi-cured sheet is 1-10 mm.
10. A copper clad laminate, characterized in that: The preparation process is as follows: 2 to 8 pieces of the prepregs according to claim 9 are taken and stacked in sequence, copper foil is covered on both sides of the prepregs, and after lamination, a copper clad laminate is prepared.